2018
DOI: 10.3390/ijms19092764
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antibacterial Adhesion When Salivary Pellicle Is Coated on Both Poly(2-hydroxyethyl-methacrylate)- and Polyethylene-glycol-methacrylate-grafted Poly(methyl methacrylate)

Abstract: Although poly(2-hydroxyethyl methacrylate) (pHEMA) and polyethylene glycol methacrylate (PEGMA) have been demonstrated to inhibit bacterial adhesion, no study has compared antibacterial adhesion when salivary pellicle is coated on polymethyl methacrylate (PMMA) grafted with pHEMA and on PMMA grafted with PEGMA. In this study, PMMA discs were fabricated from a commercial orthodontic acrylic resin system (Ortho-Jet). Attenuated total reflection-Fourier transform infrared spectra taken before and after grafting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Signals at 1080, 1025, and 813 cm −1 correspond to stretching vibrations of asymmetric and symmetric -C-O-C and Na-O, respectively [ 28 ]. Both monomers employed have C = O and C = C groups in their structure whose characteristic peaks are observed at 1718 and 1636 cm −1 in the QCL spectra ( Figure 2 b) [ 29 , 30 ] and at 1711 and 1636 cm −1 in the case of HEMA ( Figure 2 c) [ 31 , 32 ]. In the QCL spectrum, other characteristic peaks are also observed at 1478 and 1185 cm −1 , which are attributed to the bending band of quaternary ammonium groups (-N + (CH 3 ) 3 ) and the C-O of ester, respectively [ 29 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Signals at 1080, 1025, and 813 cm −1 correspond to stretching vibrations of asymmetric and symmetric -C-O-C and Na-O, respectively [ 28 ]. Both monomers employed have C = O and C = C groups in their structure whose characteristic peaks are observed at 1718 and 1636 cm −1 in the QCL spectra ( Figure 2 b) [ 29 , 30 ] and at 1711 and 1636 cm −1 in the case of HEMA ( Figure 2 c) [ 31 , 32 ]. In the QCL spectrum, other characteristic peaks are also observed at 1478 and 1185 cm −1 , which are attributed to the bending band of quaternary ammonium groups (-N + (CH 3 ) 3 ) and the C-O of ester, respectively [ 29 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Signals at 1080, 1025 and 813 cm -1 correspond to stretching vibrations of asymmetric and symmetric -C-O-C, and Na-O respectively [24]. Both monomers employed have C = O and C = C groups in their structure whose characteristic peaks are observed at 1718 and 1636 cm -1 in the QCL spectra (figure 2b) [25,26] and at 1711 and 1636 cm -1 in case of HEMA (figure 2c) [27,28]. In the QCL spectrum, other characteristic peaks are also observed at 1478 and 1185 cm -1 attributed to the bending band of quaternary ammonium groups (-N + (CH3)3) and C-O of ester, respectively [25,29].…”
Section: Ftir Spectroscopy Analysismentioning
confidence: 98%
“…Equivalent results were shown for biomaterials manufactured for oral regeneration, such as modified membranes or hydroxyapatite substitutes [76][77][78][79]. The salivary film deposited over the biomaterial surface can mediate the adhesion of important bacteria present in oral infections [68,78].…”
Section: Membranes and Bone Substitutesmentioning
confidence: 99%
“…Moreover, organic biomaterials may promote a favorable environment for bacterial metabolism due to the degradation of specific molecules compared to inorganic biomaterials or synthetic biomaterials [76]. On the other hand, Lee et al [79] revealed, using in vitro models, that their PMMA membranes possess antibacterial Promising features for dental implant surfaces have been reported to control bacterial proliferation with the application of nanotexturizations or antibiotic-loaded surfaces [72,73], suggesting a protective coating for contaminated environments. However, preclinical and clinical studies are rare regarding assays with saliva-contaminated implants associated with innovative surface treatments.…”
Section: Membranes and Bone Substitutesmentioning
confidence: 99%
See 1 more Smart Citation